2020
DOI: 10.7554/elife.54311
|View full text |Cite
|
Sign up to set email alerts
|

Integrase-RNA interactions underscore the critical role of integrase in HIV-1 virion morphogenesis

Abstract: A number of human immunodeficiency virus 1 integrase (IN) alterations, referred to as class II substitutions, exhibit pleotropic effects during virus replication. However, the underlying mechanism for the class II phenotype is not known. Here we demonstrate that all tested class II IN substitutions compromised IN-RNA binding in virions by one of three distinct mechanisms: i) markedly reducing IN levels thus precluding formation of IN complexes with viral RNA; ii) adversely affecting functional IN multimerizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(110 citation statements)
references
References 110 publications
(256 reference statements)
0
110
0
Order By: Relevance
“…This mislocalization of the RNP to a position located between the low density empty capsid (CA) core and the particle membrane in mature virions has been observed using electron microscopy ( 17 , 31 , 32 ). The buoyant sucrose gradient technique that measure the relative density of the viral core of mature virions has also been validated as an effective approach to characterize this mislocalization of the RNP ( 17 , 33 , 34 ). Here, to confirm the effect of JDH2110 on virus particle maturation, we subjected cell-free and detergent-lysed progeny virions to a linear 20 to 70% (wt/vol) sucrose gradient fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…This mislocalization of the RNP to a position located between the low density empty capsid (CA) core and the particle membrane in mature virions has been observed using electron microscopy ( 17 , 31 , 32 ). The buoyant sucrose gradient technique that measure the relative density of the viral core of mature virions has also been validated as an effective approach to characterize this mislocalization of the RNP ( 17 , 33 , 34 ). Here, to confirm the effect of JDH2110 on virus particle maturation, we subjected cell-free and detergent-lysed progeny virions to a linear 20 to 70% (wt/vol) sucrose gradient fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…Residues in the CTD of IN have also previously been identified as class II mutants that are defective for viral RNA binding and particle morphogenesis, and as a consequence the virions are defective in early steps of infection such as reverse transcription and nuclear import [ 7 ]. To determine if our mutations might display a similar phenotype we assayed the early steps of the viral life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Various residues in the CTD of IN, including some of the residues mutated in this study, have been implicated as responsible for the phenotypes of class II IN mutants [ 7 ]. When these residues were mutated, IN binding to viral RNA was disturbed leading to the formation of non-infectious viral particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have suggested that these class II mutants have defects in reverse transcription, possibly because they have lost their vRNA, or because reverse transcriptase becomes physically separated from the genetic information upon infection of a target cell ( Koneru et al, 2019 ; Madison et al, 2017 ). Now, in eLife, Sebla Kutluay of Washington University in St. Louis and colleagues – including Jennifer Elliot as first author – report how class II integrase substitutions impair the maturation of HIV-1 particles ( Elliott et al, 2020 ).…”
mentioning
confidence: 99%